A multi-layer model for e-government information security assessment - Al-Azazi , Sabri (Cranfield University, 2008)
The emphasis on the value of time from the knowledge workers and citizens has driven governments towards the transformation to the electronic method in offering government services to the public. This underpinned the need of launching e-governments worldwide. The inter-government integration, information sharing and collaboration is required to provide the citizens with well integrated services. The level of trust is one of the key factors for the integration and information sharing between the government departments. Information security contributes directly to the increased level of trust between the government departments by providing an assurance of confidentiality, integrity, and availability of sensitive governmental information. The research reported in this thesis delivers a new model that can be used as a tool to assess the level of security readiness of government departments, a checklist for the required security measures, and as a common reference for the security in the government departments in Dubai. Based on extensive literature research a new model was developed using a qualitative approach to build the overall structure and the number of layers in it. A quantitative approach was adopted during the research study to confirm the importance of the model layers and sub layers. The applicability of the model was tested and the Dubai e- government authority was taken as a case study to validate the model and its layers. The research contributes to the theoretical knowledge of the information security modelling concept in four ways. First the literature review of existing security model and their coverage of security aspects. Second, the analysis of the security threats related to the e- services. Third, the construction of a new security model based on the academic research on each layer. Fourth, the applicability of the model was in the validated case study selected.